2003
DOI: 10.1128/aac.47.8.2659-2662.2003
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B Nephrotoxicity and Efficacy against Nosocomial Infections Caused by Multiresistant Gram-Negative Bacteria

Abstract: Reported rates of nephrotoxicity associated with the systemic use of polymyxins have varied widely. The emergence of infections due to multiresistant gram-negative bacteria has necessitated the use of systemic polymyxin B once again for the treatment of such infections. We retrospectively investigated the rate of nephrotoxicity in patients receiving polymyxin B parenterally for the treatment of infections caused by multiresistant gram-negative bacteria from October 1999 to September 2000. Demographic and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
117
3
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(145 citation statements)
references
References 21 publications
18
117
3
7
Order By: Relevance
“…In previous reports, nephrotoxicity was the most common adverse effect of colistin therapy (18,20,24); however, recent studies reported lower nephrotoxicity rates in association with colistin use (14,27). In our study, we observed nephrotoxicity only in one patient which is similar to report of Falagas et al (27) in 2009.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In previous reports, nephrotoxicity was the most common adverse effect of colistin therapy (18,20,24); however, recent studies reported lower nephrotoxicity rates in association with colistin use (14,27). In our study, we observed nephrotoxicity only in one patient which is similar to report of Falagas et al (27) in 2009.…”
Section: Discussionsupporting
confidence: 79%
“…Few studies have investigated the clinical efficacy and safety of colistin use in children. It has been reported in previous studies that the effectiveness rates with colistin therapy were 47-88% (15,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, definite statements regarding the effectiveness of intravenous polymyxins as monotherapy cannot be made. [31][32][33] In a comparative observational study of intravenous colistimethate sodium versus intravenous meropenem for the treatment of intensive care unit patients with Acinetobacter baumannii ventilator-associated pneumonia, the observed outcomes, including in-hospital mortality, ventilator-associated pneumonia-related mortality and clinical cure, were comparable. 34 …”
Section: Intravenous Polymyxins In Critically Ill Patientsmentioning
confidence: 99%
“…No obstante, en la última década, ante el surgimiento y alta tasa de mortalidad en infecciones invasoras causadas por BGN-MR, polimixina B, en monoterapia o en combinación con otros antimicrobianos activos contra BGN-MR, permanece como el principal antimicrobiano usado para agentes de este tipo en nuestro medio 1,7,8 . Históricamente, la falla renal asociada al uso de polimixina B fluctúa entre 14 y 60% [8][9][10][11][12][13] . No obstante, estudios 8 www.sochinf.cl…”
Section: Introductionunclassified